The South in International Economic Regimes - Maswood, S. author. aut Link
XI, 210 p.
Keywords: Maswood examines the trade and regulatory structures that inhibit the capacity of developing countries to improve their economic conditions. In particular, the book looks at institutional structures of the WTO and examines the Doha Round negotiations to assess their success for developing countries. Developing countries have heightened expectations that these first WTO trade negotiations will deliver improved outcomes in their interest, and the book looks at difficulties in the negotiating process and prospects for global multilateralism.